Adherence to a Mediterranean diet is associated with lower incidence of frailty: A longitudinal cohort study. Issue 5 (October 2018) - Veronese, Nicola; Stubbs, Brendon; Noale, Marianna; Solmi, Marco; Rizzoli, Renè; Vaona, Alberto; Demurtas, Jacopo; Crepaldi, Gaetano; Maggi, Stefania
Summary: Background & aims: There is a paucity of data investigating the relationship between the Mediterranean diet and frailty, with no data among North American people. We aimed to investigate if adherence to a Mediterranean diet is associated with a lower incidence of frailty in a large cohort of North American people. Methods: This study included subjects at higher risk or having knee osteoarthritis. Adherence to the Mediterranean diet was evaluated using a validated Mediterranean diet score (aMED) as proposed by Panagiotakos and classified into five categories. Frailty was defined using the Study of Osteoporotic Fracture (SOF) index as the presence of ≥2 out of: (i) weight loss ≥5% between baseline and the subsequent follow-up visit; (ii) inability to do five chair stands; (iii) low energy level. Results: During the 8 years follow-up, of the 4421 participants initially included (mean age: 61.2 years, % of females = 58.0), the incidence of frailty was approximately half in those with a higher adherence to the Mediterranean diet (8 for 1000 person years) vs. those with a lower adherence (15 for 1000 persons-years). After adjusting for 10 potential confounders (age, sex, race, body mass index, education, smoking habits, yearly income, physical activity level, Charlson co-morbidity index and daily energy intake), participants with the highest aMED scores were found to have a significant reduction in incident frailty (hazard ratio = 0.71; 95% CIs: 0.50–0.99, p = 0.047) with respect to those in a lower category. Regarding individual components of the Mediterranean diet, low consumption of poultry was found to be associated with higher risk of frailty. Conclusions: A higher adherence to a Mediterranean diet was associated with a lower incidence of frailty over an 8-year follow-up period, even after adjusting for potential confounders.